Effects of high mechanical treatment and long-term annealing on crystal structure and thermal stability of Ti2O3 nanocrystals. Issue 43 (7th July 2020) - Valeeva, Albina A.; Nazarova, Svetlana Z.; Schröttner, Hartmuth; Gerasimov, Evgeny Yu.; Rempel, Andrey A.
Abstract : The effect of high-energy milling and long-term annealing on the stability of Ti2 O3 nanocrystals was studied using a magnetic susceptibility method. Abstract : The effect of high-energy milling and long-term annealing on the stability of Ti2 O3 nanocrystals was studied using a magnetic susceptibility method. In situ temperature dependences revealed that the crystal size greatly affects the magnetic susceptibility value. According to XRD, SEM and TEM data, Magnéli phases Ti9 O10, Ti4 O7, Ti7 O19 and Ti3 O5 are formed.